ALT Flare Predicts Hepatocellular Carcinoma Among Antiviral Treated Patients With Chronic Hepatitis B: A Cross-Country Cohort Study - Du, Yanan; Du, Bingying; Fang, Xiaoyan; Shu, Meng; Zhang, Yongjing; Chung, Hsingwen; Sun, Ye; Teng, Jiaming; Visalath, Phimphone; Qiu, Hong; Cai, Wei (Frontiers in Oncology, 2021)
Objectives: Alanine aminotransferase (ALT) level is one of the crucial indexes to evaluate disease status for chronic hepatitis B (CHB) patients. However, whether the ALT level after nucleos(t)ide analogue (NA) treatment is associated with hepatocellular carcinoma (HCC) development remains unclear. Materials and methods: We evaluated the association between ALT level and HCC occurrence in NA-treated patients and investigated the predictive value of ALT flare for HCC. The associations between ALT level and HCC were analyzed by logistic regression and Cox proportional hazards models. Results: There were 21,223 CHB patients at Ruijin Hospital of China and 16,737 CHB patients in the Optum electronic health records (EHR) in the United States (US) treated with NAs between 2010 and 2018. Among them, 8,152 and 4,893 patients who achieved a normal ALT value were included in the study cohorts, respectively. A significant positive dose-dependent correlation between the peak ALT level and HCC was identified in both cohorts. Within the China cohort, ALT flare was significantly associated with increased risks of HCC compared to normal ALT (HR 2.55, 95%CI 1.45-4.50). Stronger increased risks associated with ALT flare were observed in the US cohort (HR 7.62, 95%CI 4.85-11.98). Conclusions: ALT flare is a strong predictor for HCC occurrence in the CHB patients treated with NAs. Elevation of ALT, especially ALT flare warrants close monitoring for early HCC detection.